2016
DOI: 10.1002/hyp.10687
|View full text |Cite
|
Sign up to set email alerts
|

A general solution for groundwater flow in an estuarine's leaky aquifer system after considering aquifer anisotropy

Abstract: This paper presents an analytical model for describing the tidal effects in a two‐dimensional leaky confined aquifer system in an estuarine delta where ocean and river meet. This system has an unconfined aquifer on top and a confined aquifer on the bottom with an aquitard in between the two. The unconfined and confined aquifers interact with each other through leakage. It was assumed that the aquitard storage was negligible and that the leakage was linearly proportional to the head difference between the uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The most obvious difference between a confined and unconfined aquifer is that in the unconfined aquifer, when L i and L o are greater, the amplitude of the head fluctuation decays faster than during smaller leakage. The head fluctuations with different tidal‐river and inland aquitard leakage in an unconfined aquifer all propagate more than 500 m and diminish exponentially along the inland direction (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most obvious difference between a confined and unconfined aquifer is that in the unconfined aquifer, when L i and L o are greater, the amplitude of the head fluctuation decays faster than during smaller leakage. The head fluctuations with different tidal‐river and inland aquitard leakage in an unconfined aquifer all propagate more than 500 m and diminish exponentially along the inland direction (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the anisotropy of confined and unconfined aquifers have a major influence on the tide‐induced head fluctuations in an aquifer system. Chen et al () derived an analytical model for tidal effects in a two‐dimensional leaky confined aquifer system and showed that high anisotropy allowed the tidal wave to propagate further in the unconfined and confined aquifers. Figure a indicates that the larger the transmissivity T x , the stronger the wave damping effect on the head fluctuation along the x‐axis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows the correctness for the SCA. The MAE associated with the SCA is of the order of -16 10 8.9 × . It is obvious that the SCA may acquire highly accurate results.…”
Section: Numerical Examplementioning
confidence: 99%